BAURAN PEMASARAN MEMENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN ASURANSI JIWA INDIVIDU - Marwa, Sarifa; Sumarwan, Ujang; Nurmalina, Rita (Jurnal Ilmu Keluarga dan Konsumen, 2014)
This study aimed to analyze the effect of marketing mix in individual life insurance purchasing decision, as well as the marketing mix variables of the most dominant influence on the purchase decision. The results of this study can be used as a recommendation to life insurance companies in conducting marketing activities in accordance with the market needs. The study was conducted in Bogor City that had an increasing population growth in every year, was made it a good market for life insurance companies. Data for this study were obtained from 200 respondents who live in Bogor and had basic knowledge about insurance. Samples were selected based on the nonprobability sampling, with convenience sampling technique. The variable measured by even marketing mix such as price, product, person, process, promotion, physical evidence, and place. Processing and analysis of data used descriptive analysis and logistic regression analysis. This results showed that there were at least five marketing mix that had an influence on the life insurance purchase decision, and the product mix was the most influential variable on the life insurance purchase decision.